2010
DOI: 10.1161/hypertensionaha.109.139592
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Abdominal Obesity on Incidence of Adverse Metabolic Effects Associated With Antihypertensive Medications

Abstract: Abstract-We assessed adverse metabolic effects of atenolol and hydrochlorothiazide among hypertensive patients with and without abdominal obesity using data from a randomized, open-label study of hypertensive patients without evidence of cardiovascular disease or diabetes mellitus. Intervention included randomization to 25 mg of hydrochlorothiazide or 100 mg of atenolol monotherapy followed by their combination. Fasting glucose, insulin, triglycerides, high-density lipoprotein cholesterol, and uric acid levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 31 publications
2
60
3
4
Order By: Relevance
“…It has been reported that low doses of HCTZ caused hypokalemia and glucose tolerance aggravation within three months, but we showed that ARB constrained the effect of HCTZ when we changed from a common dose of ARBs to ARB with HCTZ 27,28) . The significant improvement of the urine albumin/creatinine ratio might be due to the effect of adequate lowering of blood pressure 29) .…”
Section: Discussioncontrasting
confidence: 51%
“…It has been reported that low doses of HCTZ caused hypokalemia and glucose tolerance aggravation within three months, but we showed that ARB constrained the effect of HCTZ when we changed from a common dose of ARBs to ARB with HCTZ 27,28) . The significant improvement of the urine albumin/creatinine ratio might be due to the effect of adequate lowering of blood pressure 29) .…”
Section: Discussioncontrasting
confidence: 51%
“…There are several classes of antihypertensive drugs to choose from because they are all effective in lowering BP [63] , but individualization of treatment may be necessary. Diuretics, although effective in lowering BP, may not be a good choice for hypertensive subjects with diabetes or the metabolic syndrome, because they increase blood glucose, which is associated with high incidence of cardiovascular morbidity and mortality [64][65][66] . Drugs that block the RAS such as ACEIs, ARBs, and DRIs are preferable in such cases, because they interfere with the action of angiotensin II, which is responsible for cardiovascular remodeling, new-onset diabetes mellitus, and HF (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…4,6,10,23 Such an effect occurs after short-term exposure and is more common in those with abdominal obesity. 24 This has created a dilemma when choosing appropriate therapy. Although clinicians rely heavily on the results of long-term clinical outcome studies, inevitably these do not cover all situations where a decision about drug choice is required.…”
Section: Discussionmentioning
confidence: 99%